2015
DOI: 10.1038/pr.2015.94
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal DTI early after birth predicts motor outcome in preterm infants with periventricular hemorrhagic infarction

Abstract: Background:To determine the association between early neonatal diffusion tensor imaging (DTI) and the development of unilateral spastic cerebral palsy (USCP) in preterm infants with periventricular hemorrhagic infarction (PVHI). Methods: Preterm infants with PVHI were assessed with early (≤4 wk after birth) and term-equivalent age MRI-DTI. Involvement of corticospinal tracts was assessed by visual assessment of the posterior limb of the internal capsule (PLIC) on DTI (classified asymmetrical, equivocal, or sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…De Bruïne et al [28] confirmed a strong correlation between those low FA values of the posterior limb of the internal capsule at term-equivalent age and subsequent psychomotor delay at the age of 2 years in very preterm infants. Roze et al [29] determined the association between later development of spastic CP and early perturbation of DTI values. They showed that asymmetries in FA within 4 weeks after birth were predictive of unilateral spastic CP in preterm infants with periventricular hemorrhagic infarction.…”
Section: Discussionmentioning
confidence: 99%
“…De Bruïne et al [28] confirmed a strong correlation between those low FA values of the posterior limb of the internal capsule at term-equivalent age and subsequent psychomotor delay at the age of 2 years in very preterm infants. Roze et al [29] determined the association between later development of spastic CP and early perturbation of DTI values. They showed that asymmetries in FA within 4 weeks after birth were predictive of unilateral spastic CP in preterm infants with periventricular hemorrhagic infarction.…”
Section: Discussionmentioning
confidence: 99%
“…These studies report diminished coherence of activity measured across brain circuits, indicative of weaker connectivity in individuals born preterm from infancy1112 through adulthood1314. Given the robust linkage between child neurological disorders and atypical large-scale neural connectivity1516 (see also refs 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37), theory has evolved that neurodevelopmental impairment following preterm birth may stem from alterations in neural connectivity38, and recent evidence provides nascent support for this claim1039.…”
mentioning
confidence: 99%
“…Cohorts with low prevalence of adverse motor outcomes frequently excluded infants with destructive brain lesions in recruitment . Studies with a high prevalence of CP chose study participants based on the presence of defined brain lesions …”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies from nine distinct cohorts acquired early diffusion MRI data . Sensitivity and specificity of diffusion MRI findings to determine later motor outcomes and/or CP in individual studies are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation